Na+ current expression in human atrial myofibroblasts: identity and functional roles - Koivumäki, Jussi T.; Clark, Robert B.; Belke, Darrell; Kondo, Colleen; Fedak, Paul W. M.; Maleckar, Mary M. C.; Giles, Wayne R. (Frontiers in Physiology, 2014)
In the mammalian heart fibroblasts have important functional roles in both healthy conditions and diseased states. During pathophysiological challenges, a closely related myofibroblast cell population emerges, and can have distinct and significant roles. Recently, it has been reported that human atrial myofibroblasts can express a Na+ current, INa. Some of the biophysical properties and molecular features suggest that this INa is due to expression of Nav 1.5, the same Na+ channel α subunit that generates the predominant INa in myocytes from adult mammalian heart. In principle, expression of Nav 1.5 could give rise to regenerative action potentials in the fibroblasts/myofibroblasts. This would suggest an active as opposed to passive role for fibroblasts/myofibroblasts in both the ‘trigger’ and the ‘substrate’ components of cardiac rhythm disturbances. Our goals in this preliminary study were: (i) to confirm and extend the electrophysiological characterization of INa in a human atrial fibroblast/myofibroblast cell population maintained in conventional 2-D tissue culture; (ii) to identify key molecular properties of the α and β subunits of these Na+ channel(s); (iii) to define the biophysical and pharmacological properties of this INa ; (iv) to integrate the available multi-disciplinary data, and attempt to illustrate its functional consequences, using a mathematical model in which the human atrial myocyte is coupled via connexins to fixed numbers of fibroblasts/myofibroblasts in a syncytial arrangement. Our experimental findings confirm that a significant fraction (~40-50%) of these human atrial myofibroblasts can express INa. However, our results suggest that INa may be generated by Nav 1.9, Nav 1.2, and Nav 1.5. Our findings, when complemented with mathematical modeling, provide a background for re-evaluating pharmacological management of supraventricular rhythm disorders, e.g. persistent atrial fibrillation.